Study of the effects of partial cement replacement with spent diatomaceous earth from the brewing industry in mortar - Zolin Renan; Angulski Caroline; Macanjo Debora; Meira Ana (MATEC Web of Conferences, 2025)
The present study evaluates the effect of partial replacement of cement in mortars with spent diatomaceous earth (SDE) from beer filtration, aiming to explore sustainable alternatives for civil construction. Three compositions were tested: one with 15% cement replacement by SDE, another with 5% sand replacement by SDE, and a reference composition without SDE addition. The diatomaceous earth (DE), after being used in beer filtration until saturation, was calcined in a furnace to eliminate organic matter and subsequently incorporated into the mortar composition. This research, as an extension of a previous study using residues from wine filtration, evaluates the impact of this replacement on the mechanical properties of the mortar, including compressive strength, tensile strength, and consistency. A detailed characterization of the spent diatomaceous earth was performed through X-ray diffraction and laser granulometry, enabling a better understanding of its structural properties.